Aged Human Stored Red Blood Cell Supernatant Inhibits Macrophage Phagocytosis in an HMGB1 Dependent Manner After Trauma in a Murine Model. Issue 2 (February 2017) - Zettel, Kent R.; Dyer, Mitchell; Raval, Jay S.; Wu, Xubo; Klune, John R.; Gutierrez, Andres; Triulzi, Darrell J.; Billiar, Timothy R.; Neal, Matthew D.
Abstract : ABSTRACT: Red blood cell transfusions in the setting of trauma are a double-edged sword, as it is a necessary component for life-sustaining treatment in massive hemorrhagic shock, but also associated with increased risk for nosocomial infections and immune suppression. The mechanisms surrounding this immune suppression are unclear. Using supernatant from human packed red blood cell (RBC), we demonstrate that clearance of Escherichia coli by macrophages is inhibited both in vitro and in vivo using a murine model of trauma and hemorrhagic shock. We further explore the mechanism of this inhibition by demonstrating that human-stored RBCs contain soluble high-mobility group box 1 protein (HMGB1) that increases throughout storage. HMGB1 derived from the supernatant of human-stored RBCs was shown to inhibit bacterial clearance, as neutralizing antibodies to HMGB1 restored the ability of macrophages to clear bacteria. These findings demonstrate that extracellular HMGB1 within stored RBCs could be one factor leading to immune suppression following transfusion in the trauma setting.